Factors Affecting the Preference of Orthodontic Appliances Among Undergraduate Students in West Jakarta - Kusnoto, Joko; Andayani, Lia H; Kusnoto, Budi (Journal of Dentistry Indonesia, 2023)
Malocclusion’s negative impact is not only limited to dentofacial appearance but also related to quality of life. Nowadays, orthodontic treatment can be done using conventional fixed appliances, or removable appliances called clear aligners. The preference for orthodontic appliances can be affected by several factors, including patient characteristics, self-perception, psychosocial, and oral-disorder factors. Objective: This study aims to evaluate the factors affecting the preference for orthodontic appliances among undergraduate students in West Jakarta. Methods: In this cross-sectional study, 244 undergraduate students were retrieved by purposive sampling from 7 universities located in West Jakarta. A self-administered questionnaire was used to collect data, and logistic regression analysis was carried out. Results: Fixed orthodontic appliances were commonly used (79.5%), and the majority of treatment providers were orthodontists (64.8%). Students’ belief that poor dental alignment is related to decreased social attractiveness was significantly associated with the preference for orthodontic appliances (p = 0.026; 95% CI = 1.170-11.317). Orthodontic treatment provider was significantly associated with a preference for orthodontic appliances (p = 0.000; 95% CI = 0.678-3.156). Conclusion: Fixed orthodontic appliances still become the main preference for malocclusion treatment among undergraduate students in West Jakarta. Besides that, the qualification of orthodontic treatment providers affects the preference for orthodontic appliances among undergraduate students in West Jakarta.